THE LIDI WOMEN: ECONOMIC EMPOWERMENT THROUGH NIPAH FROND CULTURAL HERITAGE IN TANJUNG PASIR COASTAL VILLAGE - Salmiah, Salmiah; Ristiliana, Ristiliana; Ramadhani, Maylisa (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This paper examines women's empowerment through the creative economy in Tanjung Pasir, Indragiri Hilir, Riau. It demonstrates how 'lidi nipah' craftswomen leverage their cultural heritage to create economically valuable handicrafts, significantly improving household economies and enabling families to meet their needs. Employing a qualitative methodology, the study utilizes observation and in-depth interviews with the craftswomen and local government officials to analyze this empowerment process.